1934
DOI: 10.1002/zaac.19342200309
|View full text |Cite
|
Sign up to set email alerts
|

Das Zustandsdiagramm des Systems Kupfer–Gallium

Abstract: α‐Phase. Feste Lösung von Gallium in Kupfer; Sättigungsgrenze bei 907° 15,7%, bei 620° 20,80% und bei 20° 21,5%. Cu‐Gitter durch Galliumzusatz mäßig aufgeweitet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1934
1934
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Lieth et al (1966Lieth et al ( , 1967 studied the phase relations in the system Ga-S using the sublimation method, and presented the P-T-X phase diagram of this binary system. Weibke (1934), Hume-Rothery & Raynor (1937) and Betterton & Hume-Rothery (1951-1952 investigated phase relations in the system Cu-Ga and showed this binary diagram from 0° to 1,100°C from the metallurgical point of view. Hahn et al (1953) fi rst synthesized CuGaS 2 phase using the evacuated silica-tube method (900°-1000°C, 12 hours heating) from a mixture of Cu 2 S and Ga 2 S 3 , and found that it has a chalcopyrite structure.…”
Section: Previous Experimental Studiesmentioning
confidence: 96%
“…Lieth et al (1966Lieth et al ( , 1967 studied the phase relations in the system Ga-S using the sublimation method, and presented the P-T-X phase diagram of this binary system. Weibke (1934), Hume-Rothery & Raynor (1937) and Betterton & Hume-Rothery (1951-1952 investigated phase relations in the system Cu-Ga and showed this binary diagram from 0° to 1,100°C from the metallurgical point of view. Hahn et al (1953) fi rst synthesized CuGaS 2 phase using the evacuated silica-tube method (900°-1000°C, 12 hours heating) from a mixture of Cu 2 S and Ga 2 S 3 , and found that it has a chalcopyrite structure.…”
Section: Previous Experimental Studiesmentioning
confidence: 96%
“…They believed that ␤ (Cu 3 Ga) had three modifications at different temperatures: ␤, ␤ and ␤ (later, ␤ and ␤ were designated as and by Hume-Rothery et al [13], respectively), and ␥ 1 , ␥ 2 and ␥ 3 were the low-tempeature modifications 0925 of the ␥ phase isostructural with the cubic Cu 9 Al 4 . Additionally, phase (CuGa 2 ) was found in the Ga-rich region [11,12], rather than the phase (∼57 at.% Ga) reported by Weibke [10]. In Hume-Rothery's work [11,12], the and phases [10] were not found.…”
Section: Literature On Phase Relationsmentioning
confidence: 87%
“…Additionally, phase (CuGa 2 ) was found in the Ga-rich region [11,12], rather than the phase (∼57 at.% Ga) reported by Weibke [10]. In Hume-Rothery's work [11,12], the and phases [10] were not found. Later, several investigations [14][15][16][17][18][19][20][21][22][23][24][25] have been reported on the Cu-Ga system and the results are similar to those of Hume-Rothery and coworkers [11,12].…”
Section: Literature On Phase Relationsmentioning
confidence: 87%
See 1 more Smart Citation
“…13) Weibke 14) noted the resemblance of the phase transformation behaviors of Cu-Ga alloys to that of Cu-Al alloys showing martensitic transformations during quenching. According to the previous work by Hames and Eppelsheimer, 15) the Cu-Ga-Mn phase alloys quenched from 750 C show martensite-like microstructures with a ferromagnetic property at room temperature.…”
Section: Introductionmentioning
confidence: 99%